2023
DOI: 10.12944/crnfsj.11.2.30
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seed Germination on Physicochemical and Bioactive Compounds Characteristics of Velvet Bean Tempe

Made Astawan,
Muhammad Ariq Faishal,
Ayu P. G. Prayudani
et al.

Abstract: Indonesia, known as the largest tempe-producing country globally with approximately 160,000 producers, faces a challenge in meeting the demand for tempe due to insufficient local soybean supply. To address this issue, Indonesia has been compelled to import significant quantities of soybeans, reaching 1.68 million tons in 2020, which escalated by 47.78% to 2.49 million tons in 2021. This study aims to scientifically investigate the impact of velvet bean seed germination on the physicochemical characteristics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The materials used in this study were Genetically Modified Organism (GMO) soybeans (Sb&B Food Inc., Casselton, United States), and velvet bean seeds purchased from PT. Nagari Bumi Asri (Yogyakarta, Indonesia) with a chemical composition that can be seen in our previous study (3), Raprima ® tempe starter (Bandung, Indonesia), and polypropylene plastic as tempe packaging. Moreover, the materials used for analysis consisted of reagents for proximate analysis, 1-diphenyl-2-picrylhydrazyl (DPPH), ascorbic acid, Folin-Ciocalteu, and gallic acid from Sigma-Aldrich (United States).…”
Section: Chemicals and Materialsmentioning
confidence: 82%
See 3 more Smart Citations
“…The materials used in this study were Genetically Modified Organism (GMO) soybeans (Sb&B Food Inc., Casselton, United States), and velvet bean seeds purchased from PT. Nagari Bumi Asri (Yogyakarta, Indonesia) with a chemical composition that can be seen in our previous study (3), Raprima ® tempe starter (Bandung, Indonesia), and polypropylene plastic as tempe packaging. Moreover, the materials used for analysis consisted of reagents for proximate analysis, 1-diphenyl-2-picrylhydrazyl (DPPH), ascorbic acid, Folin-Ciocalteu, and gallic acid from Sigma-Aldrich (United States).…”
Section: Chemicals and Materialsmentioning
confidence: 82%
“…These enzymes facilitate the conversion of polyphenolic compounds into quinone group compounds, contributing to the seeds’ dark colour ( 24 ). In addition, according to Astawan et al ( 3 ), the reduced lightness observed in germinated velvet bean and soybean tempe is caused by the high concentration of amino acids in the seeds that result from the germination process. When the seeds undergo heating or boiling during tempe production, these amino acids undergo non-enzymatic browning, such as the Maillard reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations